Knowledge In Renal Nutrition Of Medical Doctors And Nursing Staff - Ong Sik Yin; Magdalin Cheong (The Korean Society of Nephrology, 2012)
Diet prescription for hospitalized renal patients should be individualized and based on their nutritional status and biochemical profiles. However the practice of ordering a 'renal diet' which consists of low protein, low salt, low potassium and low phosphate for all renal patients is common in the acute hospital setting. A total of 49 medical doctors were interviewed on their diet prescription practices for renal patients. In addition, a questionnaire was distributed to 488 nurses to assess their knowledge in renal nutrition. 68% of house officers (first year residents) reported that a 'renal diet' should be low in protein, salt, potassium, phosphate but only 38% of medical officers reported the same. While 100% of medical doctors stated that renal patients are at risk of compromised nutrition, only 45% of them would refer all renal patients to a dietitian. 47% of nurses believed that 'renal diet' low in potassium, salt, phosphate and protein should be prescribed to all patients with chronic renal failure. Only 38% of nurses were aware of the need for higher protein diet for patients on dialysis. In conclusion, there is a need to improve the knowledge of medical doctors and nursing staff in renal nutrition.